Achieving very high cycle fatigue performance of Au thin films for flexible electronic applications. (30th October 2021) - Chen, Hong-Lei; Luo, Xue-Mei; Wang, Dong; Schaaf, Peter; Zhang, Guang-Ping
Graphical abstract: Highlights: The very high-cycle fatigue performance of Au films is significantly enhanced in supported loading by adding an ultrathin Ti interlayer at the Au film/polyimide interface. The typical intrusion-like voids beneath the surface extrusions in polymer-supported Au films is suppressed at the Au/Ti interface. The reduction of cyclic strain localization degree can be realized by the addition of Ti interlayer in Au/Ti films. Abstract: The fatigue damage behavior of the nanocrystalline Au films on polyimide substrates was investigated. It was found that the very high-cycle fatigue damage resistance of the Au film was significantly enhanced by at least a factor of ∼2 in supported loading through adding an ultrathin Ti interlayer at the Au film/polyimide interface. Such a better fatigue damage resistance is mainly ascribed to the effective suppression of voiding at the Au film/polyimide interface through modulation of the Au/Ti interface, and thus the propensity of the cyclic strain localization and grain boundary cracking is reduced. The finding may provide a potential strategy for the design of flexible devices with ultra-long fatigue life.